Behavioral analysis in the development of Chicken To Go Padang - Sagitri, Afreliya; Sarla Atova, Latansa; Sakinah, Atifah; Beliya, Stafini; Nila Sari, Vivi (AMK : Abdi Masyarakat UIKA, 2023)
The development of Chickhen to Go Padang is a process that involves various aspects, including behaviors that affect its success. This study aims to analyze behaviors related to the development of Chickhen to Go Padang, including consumer behavior, business behavior, and its impact on business growth. This study reviews consumer behavior in the context of the development of Chickhen to Go Padang. Research on consumer behavior can provide insight into factors that influence customer purchasing decisions, such as taste, price, location, and previous customer experience, business owners must understand market trends, innovate menus, and carry out effective marketing strategies to attract customers and maintain market share. Business behavior analysis also includes aspects of leadership, decision making, and resource management to achieve sustainable growth. This study also illustrates the impact of behavior in the development of Chickhen to Go Padang. By understanding the behavior of consumers and business actors, it can be known the factors that affect business success. Increased customer satisfaction, loyalty, and positive reputation will have an impact on business growth and potential expansion into a wider market. In conclusion, this study emphasizes the importance of analyzing behavior in the development of Chickhen to Go Padang. Understanding the behavior of consumers and business actors helps in making the right decisions to increase competitiveness and business success. Behavioral analysis also gains insights into market trends, consumer preferences, and business development opportunities that can strengthen Chickhen to Go Padang's position in the fast food industry.